2003
DOI: 10.1097/01.asn.0000060573.77611.73
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors Are Differently Associated with Urinary Albumin Excretion in Men and Women

Abstract: Abstract. Cardiovascular morbidity and mortality is not equally distributed among genders, men being more affected than women. It is not clear whether this is only related to a higher prevalence of the cardiovascular risk factors or to a similar prevalence of the risk factors as in women but a greater vascular susceptibility to these risk factors in men. This was tested by studying the association between various cardiovascular risk factors and urinary albumin excretion (UAE) in a large cohort of male and fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
65
0
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 21 publications
12
65
0
5
Order By: Relevance
“…The growing prevalence of diabetes in our study population and especially in the Southern population is likely due to the increased prevalence of obesity (23,26) . In addition, consistent with previous studies (8,17,27) , men showed a higher prevalence of diabetes and hyperglycaemia than women, while women showed a higher prevalence of dyslipidaemia than men (28) .…”
Section: Discussionsupporting
confidence: 92%
“…The growing prevalence of diabetes in our study population and especially in the Southern population is likely due to the increased prevalence of obesity (23,26) . In addition, consistent with previous studies (8,17,27) , men showed a higher prevalence of diabetes and hyperglycaemia than women, while women showed a higher prevalence of dyslipidaemia than men (28) .…”
Section: Discussionsupporting
confidence: 92%
“…We did not find sex to be a significant predictor of AER in either cohort, in contrast with studies in adults showing AER and MA to be higher in males (33,34). Our findings are consistent with other studies in both healthy and T1DM children (35)(36)(37)(38).…”
Section: Discussionsupporting
confidence: 86%
“…28 Consistent with the findings in the present study, De Cosmo et al 29 showed that, in patients with type 2 diabetes, increased urinary albumin excretion is associated with cardiovascular risk factors, which is significantly higher in men than in women. In a study on healthy individuals, Verhave et al 30 showed that cardiovascular risk factors and urinary albumin excretion rate are significantly correlated only in men. This is the first study demonstrating the effect of gender on the albuminuria-ischemic heart disease relationship in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%